(untitled) (Latakia University Journal -Biological Sciences Series, 2014)
خُزنت البسطرمة المصنعة من لحم البقر ودهن البطن وبنسبة 3 لحم:1 دهن, تحت التبريد (4 ±2مﹾ ), لمدد زمنية (0, 15, 30, 60, 120, 180 أيام), وتمت دراسة تأثير مدة التخزين على أهم الخصائص الكيميائية, الميكروبية, الحسية للبسطرمة. أظهرت نتائج التحاليل الكيميائية أن البسطرمة المدروسة تحقق المواصفة القياسية السورية, من حيث نسبة ملح الطعام ونسبة الدهن, وتقترب من تحقيقها في نسبة الرطوبة, كما بينت حصول انخفاض بسيط في نسبة الرطوبة, الدهن والبروتين, وارتفاع كل من الحموضة, نسبة الآزوت الطيار الكلي, الآزوت الذائب ورقم البيروكسيد في البسطرمة مع تقدم مدة التخزين على درجة حرارة (4 ±2مﹾ ). كما بينت الاختبارات الميكروبية خلو البسطرمة من بعض الأحياء الممرضة, وخاصة السالمونيلا والـ E.coli, وبينت أيضاً أن التعداد الكلي للبكتريا الهوائية والخمائر والفطور كان ضمن حدود المواصفة القياسية السورية, كما أظهرت النتائج حصول تدهور في الخصائص الميكروبية للبسطرمة المخزنة مع تقدم الزمن, حيث أصبحت البسطرمة غير صالحة للاستهلاك من الناحية الميكروبية بعد شهرين من التخزين نتيجة الارتفاع الكبير لأعداد البكتريا الهوائية والخمائر والفطور. كما بينت نتائج الاختبارات الحسية حصول تدهور في الخصائص الحسية مع تقدم زمن التخزين, وكان التدهور واضحاً بعد التخزين لمدة شهرين وخاصة الطعم, اللون, الرائحة والقوام, فقد أصبحت البسطرمة غير مقبولة حسياً. Pastrami, manufactured from beef and abdominal fat and of a ratio of 3 meat to 1 fat, was stored under refrigeration at (4±2 ˚C) and storage times (0, 15, 30, 60, 120, and 180 days). The effects of storage times on the most important chemical, microbiological and sensory properties of pastrami were investigated. The results of chemical analyzes showed that the studied pastrami conformed to the Syrian Standards in terms of the proportion of salt and fat content, and it nearly conformed to the standards in terms of humidity. The results also showed a slight decrease in the percentage of moisture, fat and protein, and an increase in each of the acidity, proportion of total volatile nitrogen, soluble nitrogen and peroxide value in pastrami with the progress of the storage period at the temperature degree (4±2 ˚C). The microbial tests showed that pastrami is free from some sickening organisms especially salmonella and E. coli. It also showed that the census of the aerobic bacteria, yeasts and fungi was within the limits of the Syrian standards. The results showed deterioration in the microbial properties of stored pastrami with the progress of time; pastrami became invalid from a microbial point of consumption after two months of storage as a result of the big number of aerobic bacteria, yeasts and fungi. The sensory tests showed deterioration in the organoleptic characteristics of storage with the progress of time, the deterioration was clear after two months of storage; pastrami became unacceptable in terms of taste, color, smell and texture.